Processing Information about Support Exchanges in Close Relationships: The Role of a Knowledge Structure - Turan, Bulent (Frontiers in Psychology, 2016)
People develop knowledge of interpersonal interaction patterns (e.g., prototypes and schemas), which shape how they process incoming information. One such knowledge structure based on attachment theory was examined: the secure base script (the prototypic sequence of events when an attachment figure comforts a close relationship partner in distress). In two studies (N = 53 and N = 119), participants were shown animated film clips in which geometric figures depicted the secure base script and asked to describe the animations. Both studies found that many people readily recognize the secure-base script from these minimal cues quite well, suggesting that this script is not only available in the context of specific relationships (i.e., a relationship-specific knowledge): The generalized (abstract) structure of the script is also readily accessible, which would make it possible to apply it to any relationship (including new relationships). Regression analyses suggested that participants who recognized the script were more likely to (a) include more animation elements when describing the animations, (b) see a common theme in different animations, (c) create better organized stories, and (d) later recall more details of the animations. These findings suggest that access to this knowledge structure helps a person organize and remember relevant incoming information. Furthermore, in both Study 1 and Study 2, individual differences in the ready recognition of the script were associated with individual differences in having access to another related knowledge: indicators suggesting that a potential relationship partner can be trusted to be supportive and responsive at times of stress. Results of Study 2 also suggest that recognizing the script is associated with those items of an attachment measure that concern giving and receiving support. Thus, these knowledge structures may shape how people process support-relevant information in their everyday lives, potentially affecting relationship outcomes and mental and physical health.